Ethanol induction of FGF21 in the liver is dependent on histone acetylation and ligand activation of ChREBP by glycerol-3-phosphate - Mi Cheong Cheong; Bryan Mackowiak; Hyung Bum Kim; Genaro Hernandez; Tulip Nandu; Kevin Vale; Yuan Zhang; Lauren G. Zacharias; Thomas P. Mathews; Bin Gao; W. Lee Kraus; Steven A. Kliewer; et al. (Proceedings of the National Academy of Sciences, 2025)
Ethanol rapidly stimulates the liver to synthesize the hormone fibroblast growth factor 21 (FGF21), which then acts on the brain to elicit a multifaceted protective response. We show that in mice, this induction of FGF21 occurs at the level of gene transcription and is regulated by two byproducts of ethanol metabolism, glycerol-3-phosphate (G3P) and acetyl-CoA. Using cell-based reporter and thermal shift binding assays, we show that G3P binds to a conserved domain and activates the transcription factor carbohydrate-responsive element-binding protein (ChREBP), which regulates the Fgf21 gene promoter. The stimulation of Fgf21 gene transcription by ethanol also requires its metabolism to acetyl-CoA and correlates with histone acetylation. Accordingly, a p300/CBP histone acetyltransferase inhibitor blocks histone acetylation, ChREBP recruitment, and transcriptional activation at the Fgf21 promoter. Together, these findings reveal a dual regulatory mechanism driven by both G3P and acetyl-CoA that explains ethanol’s robust stimulatory effect on Fgf21 and possibly other ChREBP target genes in the liver.